Positive Fecal Immunochemical Test Strongly Predicts Adenomas in Younger Adults With Fatty Liver and Metabolic Syndrome. Issue 2 (3rd February 2021) - Yeh, Jen-Hao; Lin, Chih-Wen; Wang, Wen-Lun; Lee, Ching-Tai; Chen, Jen-Chieh; Hsu, Chia-Chang; Wang, Jaw-Yuan
Abstract : INTRODUCTION: The incidence of early-onset colorectal cancer is increasing. This study explored the feasibility of fecal immunochemical test (FIT) and risk factors for predicting colorectal neoplasm in younger adults. METHODS: This single-center study included 6, 457 participants who underwent health examination from 2013 to 2016 including index colonoscopy (3, 307 individuals aged 30–49 years as the younger adult group and 3, 150 aged ≥50 years as the average-risk group). Primary outcomes were adenoma detection rate (ADR) and advanced ADR (AADR). Findings of younger participants were stratified by the results of FIT and clinical risk factors and were compared with those of the average-risk group. RESULTS: Among participants aged 30–49 years, a positive FIT was associated with significantly higher ADR (28.5% vs 15.5, P < 0.001) and AADR (14.5% vs 3.7%, P < 0.001) than a negative FIT. Moreover, a positive FIT was associated with higher AADR in younger participants than in average-risk counterparts (14.5% vs 9.8%, P = 0.028). Although no single risk factor predicted FIT positivity in younger participants, nonalcoholic fatty liver disease was independently associated with higher ADR (odds ratio = 2.60, 95% confidence interval = 1.27–5.34, P = 0.001), and metabolic syndrome was independently predictive of higher AADR in younger participants than in average-risk participants (odds ratio = 3.46, 95% confidence interval = 1.66–7.21, P = 0.001). DISCUSSION: A positive FIT in people aged 30–49 years implies a higher risk of colorectal neoplasm, particularly among patients with nonalcoholic fatty liver disease and metabolic syndrome.